Quality of Life Indicators in Sustainable Urban Areas - Abunazel, Ahmed; Hammad, Yasmin; Abd AlAziz, Mohamed; Gouda, Essam; Anis, Wagdy (ARCHive-SR, 2019)
Quality of life is a concept that has been discussed recently in various studies, as a response to many problems facing the compacted cities, all over the world as well as in Egypt. The purpose of this paper is to concentrate mainly on the concept of urban quality of life, it has a multi-dimensional and complex issue, the framework of this study is to find the (missing available urban quality of life indicators) in compacted cities. Although, there were design concepts of sustainable urban form in (High-density residential areas) with mixed land uses, which have a high degree of social interaction, this paper also aims to facilitate the participation of urban authorities in process of measuring, and analyzing the urban quality of life with providing an extra element for design concepts of a sustainable urban area such as greening & renewable energy. The study is beneficial for who interested in the field of sustainable development, and it gives indicators such as (GDP) (gross domestic product) which help the Simi sustainable areas to be a more efficient with urban quality of life indicators. GDP is highly useful for measuring marketing production and providing an indicative snapshot of an economy at a given time, this research uses the descriptive analytical and statistical approach to identify a quality of life indicators through study the Interrelationships environmental, social, economic and physical elements applying on compacted Egyptian cities. Finally, to raise the value of benefit from the resources and sustainable development within the compacted residential areas to get the required indicators of quality of urban life and managed.